ANALISA HUKUM WARIS ADAT BALI TERHADAP PEWARISAN WANITA HINDU BALI - Matthew Jeremia; Michael Michael; Martin Izha Mahendra; Jeane N. Selly (Sabtida, 2023)
This research aims to analyze the Balinese Customary Inheritance Law in the context of inheritance for Hindu women in Bali. The Balinese customary inheritance law has a strong tradition and significant influence on the distribution of inherited wealth among the Hindu community in Bali. This research explains the principle of